A comprehensive review of greenhouse gas based on subject categories - Chen, Ru; Kong, Ying (The Science of the total environment, 2023)
Greenhouse gas (GHG) concentrations have continued to increase in the atmosphere and unequivocally warmed the climate system, and human activities contribute significantly to the growth impact. Various research puzzles and potential mitigation evidence involving GHG related research (GRR) need to be explored and deciphered from large-scale literature records to provide a whole picture and clear scientific view on the current state of GRR to promoting action on climate change. By combining Bibexcel-based bibliometrics with Pajek's social network analysis, we explore the literature statistics and interdisciplinary characteristics of GRR, and identify frequently debated topics in interdisciplinary by going deep into the texts of those classical literature. We found the trend of GRR's publications in the Environmental/Ecology group increased exponentially with an annual growth rate of 47.3 % and continue to expand in 13 subject categories. There are four types of relationships in the author cooperation, which gradually promote the cross-study of GHG in different subject categories, and the regional cooperation relations are relatively stable involving North America, Asia, Europe, Oceania, and South America. Those classical literature are widely distributed in six interdisciplinary categories, specifically ‘Agronomy, Forestry and Zoology’, ‘Biodiversity Conservation and Ecology’, ‘Engineering, Environmental and Green & Sustainable Science & Technology’, ‘Geography and Remote Sensing’, ‘Limnology, Marine & Freshwater Biology and Water Resources’, and ‘Public, Environmental & Occupational Health’. [Display omitted] •A comprehensive review of GHG related research (GRR) with bibliometrics•Publications of GRR in the Environmental/Ecology group increased exponentially.•4 types of author cooperation relations promote GRR in 13 subject categories.•Regional cooperation relations of GRR are relatively stable around the world.•Classical literature are widely distributed in 6 interdisciplinary categories.